2017
DOI: 10.1038/srep42094
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of mRNA and miRNA identifies dehydration and salinity responsive key molecular players in citrus roots

Abstract: Citrus is one of the most economically important fruit crops around world. Drought and salinity stresses adversely affected its productivity and fruit quality. However, the genetic regulatory networks and signaling pathways involved in drought and salinity remain to be elucidated. With RNA-seq and sRNA-seq, an integrative analysis of miRNA and mRNA expression profiling and their regulatory networks were conducted using citrus roots subjected to dehydration and salt treatment. Differentially expressed (DE) mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 93 publications
(107 reference statements)
5
36
0
Order By: Relevance
“…with salt tolerance, abiotic stresses in rice, and other crops. Manu Kumar et al elaborated on the relationship of OsSta2 with salt tolerance and abiotic stress in rice [52][53][54][55][56][57][58]. Salt tolerant varieties can be produced using marker-assisted selection or genetic engineering by introducing salt-tolerance genes [43].…”
Section: Discussionmentioning
confidence: 99%
“…with salt tolerance, abiotic stresses in rice, and other crops. Manu Kumar et al elaborated on the relationship of OsSta2 with salt tolerance and abiotic stress in rice [52][53][54][55][56][57][58]. Salt tolerant varieties can be produced using marker-assisted selection or genetic engineering by introducing salt-tolerance genes [43].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the morphological changes were consistent with previous observations, and a large number of DEGs and DE miRNAs were identified. Some reports have demonstrated that the miRNA-mRNA regulatory network responds to abiotic stress (Xie et al, 2017). In this work, we attempted to construct a low-Pi-induced miRNA-mRNA regulatory network according to the DEG and DE miRNA datasets.…”
Section: Discussion 10mentioning
confidence: 99%
“…A large body of evidence has shown that miRNA-mediated posttranscriptional regulation plays a fundamental role in plant responses to stressful factors, including pathogen infection, salt, drought, heat, cold, nutrient deficiency and metal toxicity [81][82][83][84][85][86]. A great deal of effort has been focused on the identification and functional analysis of plant miRNAs in response to the infection of pathogens, such as viruses [87][88][89], bacteria [16,[90][91][92] and fungi [13,93,94], which have provided valuable information as to the role miRNAs play in plant-pathogen interactions [95,96].…”
Section: Discussionmentioning
confidence: 99%